2010
DOI: 10.1108/02637471011086554
|View full text |Cite
|
Sign up to set email alerts
|

Forces for change in property education and research in Australia

Abstract: PurposeThis paper aims to identify changes occurring within the property professions and at the same time focus on the changing structures of the tertiary education sector in Australia and how both of these will influence property/real estate education and research into the future.Design/methodology/ approachThe paper reviews a range of published international material and conference papers mostly emanating from the Pacific Rim Real Estate Society (PRRES) a formal focus for property researchers, educators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…However, the property discipline as an area of study is still relatively small-scale, and remarkably under-represented in public funding. Except for those closely involved in the relevant profession, property as a discipline also lacks recognition (Hefferan and Ross, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the property discipline as an area of study is still relatively small-scale, and remarkably under-represented in public funding. Except for those closely involved in the relevant profession, property as a discipline also lacks recognition (Hefferan and Ross, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is no lack of research discussing the need for reform of property education in Australia in order to meet changing demands in the property sector (Boyd, 2007;Hefferan, 2011;Hefferan and Ross, 2010;Parker, 2012). Criticism of existing property courses centres around the fact that they may not meet the requirements of the broader property industry, or the senior management of universities seeking to implement federal government education policy (Parker, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a good way to deliver commercial awareness is to provide students with simulated or real-life practical experience. The RICS-accredited course directors' emphasis on the incorporation 422 ET 57,4 of practical experience as part of the curriculum highlights the fact that academics are as concerned with the delivery mechanism as with the content of the curriculum, which in turn shows that the academic respondents of this study have implemented Yu's (2001), Baxter's (2007) and Hefferan and Ross's (2010) suggestions regarding the need to 'consider the delivery method, and the teaching and learning pedagogy in property course curriculums'. It is essential for universities to engage with employers and practitioners in order to create opportunities for students to gain practical experience through, for example, placements and internships.…”
Section: How Should Rics-accredited Property Courses Be Designed So Tmentioning
confidence: 94%
“…Yu (2001) commented that real estate curricula should consider the inclusion of subjects outside their areas of specialisation in order to equip students to be better prepared for change. Hefferan and Ross (2010) and Hefferan (2011) reinforced Yu's (2001) comments and identified the forces, which drive the change in property education and research, and in the strategic directions of teaching and research. Hefferan (2011) concluded that the curricula of property and real estate education should encompass a wider base and extend beyond the traditional valuation and analysis field, but that certain universities tend to focus on specialist areas as a result of significant emerging changes in the tertiary education sector.…”
mentioning
confidence: 91%
“…However the fundamental valuation skills underpinning the profession will likely remain relevant, whilst the nature of the future work is anticipated to involve complex paradigms (Hefferan and Ross, 2010;Hefferan, 2011). Therefore it can be inferred that Valuers need to develop a broader, adaptable and flexible skill set, rather than one particular narrow skill set (Susskind and Susskind, 2015).…”
Section: Current Professional Issuesmentioning
confidence: 99%